2018
DOI: 10.18203/issn.2454-2156.intjscirep20182206
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer among young girls: a KAP study conducted in Lahore

Abstract: <p class="abstract"><strong>Background:</strong> Breast cancer is the second most frequently occurring malignant tumour. It's a progressive disease hence gradually developing into more fatal form from very small lesion. Knowledge and awareness about risk factors, symptoms and screening methods reduces the mortality and morbidity.</p><p class="abstract"><strong>Methods:</strong> A cross-sectional study was conducted in Lahore. Data was collected anonymously on self-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
6
1
Order By: Relevance
“…Majority of them indicated education, internet, TV and university as their main source of information on breast cancer. This is similar to the finding by Khalid et al (2018) on Breast cancer among young girls: a KAP study conducted in Lahore which revealed that Internet, TV, breast cancer campaigns, friends and relatives and health professionals are their major source of information on breast cancer 11 .…”
Section: Discussionsupporting
confidence: 87%
“…Majority of them indicated education, internet, TV and university as their main source of information on breast cancer. This is similar to the finding by Khalid et al (2018) on Breast cancer among young girls: a KAP study conducted in Lahore which revealed that Internet, TV, breast cancer campaigns, friends and relatives and health professionals are their major source of information on breast cancer 11 .…”
Section: Discussionsupporting
confidence: 87%
“…10,[14][15][16] On the contrary, majority of the study participants in few other studies done in different parts of the country have quoted family history of breast cancer as the major risk factor. [17][18][19][20] When asked about symptoms, majority mentioned any mass/lump in the breast followed by pain in line with the findings of many other studies. 8,11,14,15,20 Regular exercise was considered as one of the major protective factor against the occurrence of breast cancer by more than 60% of study participants in the present study in confirmation to the findings of other studies.…”
Section: Discussionsupporting
confidence: 60%
“…8,11,14,15,20 Regular exercise was considered as one of the major protective factor against the occurrence of breast cancer by more than 60% of study participants in the present study in confirmation to the findings of other studies. 10,12,18 More than half of the participants in present study believed that they are not at risk and remaining were unaware but none positively believed that they are at risk of developing breast cancer. But still, majority i.e.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Study conducted to assess the knowledge, attitude and practice of BSE among females in medical and non-medical colleges in Qassim University showed that both the categories of the students do have a positive level of knowledge regarding BSE, even though they lack at practicing it [8]. The cross-sectional study on breast cancer among young girls in Lahore there is a lack of knowledge and awareness regarding breast cancer and its screening methods is present among young girls [9]. A similar cross-sectional study for evaluation of breast cancer awareness among female university students in Zarqa University, Jordan shows that 88% of them had poor levels of awareness of breast cancer scale, 56% had knowledge about breast cancer symptoms, 90% had knowledge about risk factors of breast cancer and 72% had high and medium attitude towards breast cancer treatments.…”
Section: Introductionmentioning
confidence: 99%